2004
DOI: 10.1021/jf0307550
|View full text |Cite
|
Sign up to set email alerts
|

Total Oxidant Scavenging Capacities of Common European Fruit and Vegetable Juices

Abstract: The total oxidant scavenging capacity (TOSC) assay in a modified and automated version was applied for a comparative and detailed survey of the antioxidant capacities of 14 common European fruit and vegetable juices (ACE, apple, beetroot, blueberry, carrot, elderberry, lemon, lingonberry, multivitamin, orange, pink grapefruit, sauerkraut, and tomato juices as well as sour cherry nectar). The juices were ranked according to their scavenging capacity against the three reactive oxygen species (ROS) peroxyl and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 40 publications
(54 reference statements)
0
47
0
4
Order By: Relevance
“…Content of total phenols in apple juice was lesser ranging from 331 mg/l in Selena variety up to 697 mg/l in Melodie variety. Lichtenhäler and Marx (2005) evaluated total oxidant scavenging capacity of apple juices in comparison with common European fruit and vegetable juices as average for hydroxyl radicals and apple, tomato, carrot, and sauerkraut juices were classified into the group with even lower antioxidant capacities against peroxyl radicals and peroxynitrite. Thielen et al (2004) also confirmed a huge variation of polyphenol amounts (89-437 mg/l) and Kahle et al (2005) estimated 154-178 mg/l for dessert apple juices, whereas for "old" German cider apple va-rieties 261-970 mg/l were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Content of total phenols in apple juice was lesser ranging from 331 mg/l in Selena variety up to 697 mg/l in Melodie variety. Lichtenhäler and Marx (2005) evaluated total oxidant scavenging capacity of apple juices in comparison with common European fruit and vegetable juices as average for hydroxyl radicals and apple, tomato, carrot, and sauerkraut juices were classified into the group with even lower antioxidant capacities against peroxyl radicals and peroxynitrite. Thielen et al (2004) also confirmed a huge variation of polyphenol amounts (89-437 mg/l) and Kahle et al (2005) estimated 154-178 mg/l for dessert apple juices, whereas for "old" German cider apple va-rieties 261-970 mg/l were determined.…”
Section: Resultsmentioning
confidence: 99%
“…quercetin), vitamin C (ascorbic acid), and other polyphenols have extremely effective antioxidant properties. 30 It has been increasingly appreciated that drinking BRJ promotes healthy benefits to cardiovascular system. Clinical studies in hypertensive patients showed that chronic ingestion of BRJ significantly lowered blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological studies have shown that the diet with high fruits and vegetables has potential to protect the human body against Reactive Oxygen Species mediated damage. In the recent years the investigations have indicated that the antioxidant properties of the fruits and vegetables are due to presence of high amounts of known antioxidants such as polyphenols, vitamin C, vitamin E, -carotene, and lycopene [21]. Besides possessing antioxidant properties, ascorbic acid (vitamin C) also plays a key role in collagen biosynthesis, iron absorption, immune response activation, wound healing, and osteogenesis [22].…”
Section: Introductionmentioning
confidence: 99%